2018
DOI: 10.1002/jhrm.21329
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining and spreading quality improvement: Decreasing intrapartum malpractice risk

Abstract: The multilevel integrated practice and coordinated communication model was successfully spread and sustained. Key elements contributing to this success included developing and maintaining evidence-based guidelines, ensuring leadership buy-in and support, collecting and reporting performance measures, holding teams accountable, providing training, and ensuring transparent communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…In addition, health care organizations continue to struggle with sustaining improvement gained through project work. 14–18 We found that implementing an RPI program not only addressed these gaps by providing the training to increase confidence and knowledge for improvement work but led to sustainable improvements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, health care organizations continue to struggle with sustaining improvement gained through project work. 14–18 We found that implementing an RPI program not only addressed these gaps by providing the training to increase confidence and knowledge for improvement work but led to sustainable improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Health care organizations also continue to have challenges sustaining improvements; this has had a detrimental effect on their ability to pursue high reliability. 14 , 15 A full third of quality improvement projects are not sustained after a year and almost 70% are not sustained over time. 16 , 17 Our understanding about what leads to sustainability is not yet well developed, but change management is likely a key factor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other articles in this issue present timely learning opportunities, including: A novel anesthesiologist‐led multidisciplinary model for evaluating high‐risk surgical patients at a comprehensive cancer center Sustaining and spreading quality improvement: Decreasing intrapartum malpractice risk Implementing safety hotlines: Stamford Health's experience and future opportunities …”
mentioning
confidence: 99%